Analysis of Factors Affecting Consumer Interest In Urban Are-as In Shopping For Daily Necessities Online During The Covid-19 Pandemic - Prayandi, Calvin; Pradipta, Imran; Rizki, Muhammad; Manaf, Peri Akbar (Green Publisher Indonesia, 2023)
Online Shopping is the act of buying products and services through an online store or e-commerce. The culture of online shopping in Indonesia began to develop around the 2000s with the introduction of the internet. One of the benefits obtained by online shopping is that it makes shopping easier and more practical. Buyers do not need to spend time and spend on a trip to a physical store. It has also created a change in one's behavior in shopping. The purpose of this research is to find out daily needs during the Covid-19 pandemic. This research is a quantitative study in which a systematic empirical investigation of phenomena that can be observed using statistical, mathematical, or computational techniques is carried out. Predefined and highly structured data collection techniques are a major factor in quantitative research design when associated with positivis. this study shows what factors influence buyers' interest in buying a product at Online Groceries during the pandemic. And from the results of our research shows that one of the accepted and most significant factors influencing buyers' interest in buying at Online Groceries is from their Effort Expectancy